Productivity Analysis PC-300 and PC-400 in Earthworks at a Gold Mining Project in Indonesia - Fahmi, Muhammad; Ghuzdewan, Toriq Arif (Journal of the Civil Engineering Forum, 2023)
Material movement is a significant and costly aspect of gold or general mining projects. This involves the utilization of expensive heavy equipment, necessitating careful management to ensure optimal efficiency. Therefore, this study aimed to analyze the productivity of excavators PC-300 and PC-400 as well as compare theoretical calculation results with actual conditions. The basis was formed by real field data, collected by earthwork supervisors at a gold mine in Indonesia. This data encompassed daily heavy equipment usage, including the duration, the quantity of material moved, and the types of material involved in the relocation process. The calculations resulted in theoretical productivity of 121.45 m3 hour-1 and 99.56 m3 hour-1 for PC-400 and PC-300. Meanwhile, the calculations based on actual conditions resulted in an average productivity of 114.4 m3 hour-1 and 66.3 m3 hour-1 for PC-400 and PC-300 during a one-year project period. The difference between actual and theoretical productivity for PC-400 and PC-300 was relatively small and large at -7.05 m3 hour-1 and -33.26 m3 hour-1, with 0.94 and 0.64 match factors, respectively. The large difference in productivity for the PC-300 was because the equipment supported work projects, such as opening work area access, maintaining area of work, and serving as supporting equipment. Furthermore, it occurred in the total actual production of the material movement against the one-year target production, which was less than -31,921 m3 (-2.5%) out of the 1,277,325 m3 total. The production deficit was attributed to a construction failure that caused PC-400 and PC-300 to be temporarily relocated for reparation. Based on the simulation, target production was achieved by the actual condition at month 13 (additional 1-month duration) with a total production of 1,283,856 m3, which obtained more than +6,531 m3 (+0.51%).